Melampaui Banjir sebagai Bencana Alam: Perampasan Struktural atas Hak Hidup Layak sebagai Konsekuensi Kebijakan Konsesi Lahan: Beyond Floods as Natural Disasters: Structural Deprivation of the Right to a Decent Life as a Consequence of Land Concession Policies - Sugiyanto, Sugiyanto; Thoif, Mokh. (Perspektif Hukum, 2026)
The flash floods that occurred on 26 November 2025 in Aceh, West Sumatra, and North Sumatra not only resulted in loss of life and widespread physical destruction, but also led to the systemic loss of living space, livelihoods, and a sense of security among affected communities. This article aims to examine the potential for structural deprivation of the right to an adequate standard of living as a consequence of land concession policies underlying the occurrence of flash floods in these three provinces. This study employs a normative-critical approach grounded in human rights and environmental justice, drawing upon recent scholarly developments on disaster risk, land use, and state obligations under international human rights law. The findings indicate that flash floods cannot be understood merely as natural events caused by extreme rainfall, but rather as risks produced through policy-driven mechanisms, particularly risk amplification resulting from land-use change, followed by risk transfer from economic actors to downstream communities. This process generates environmental injustice, manifested in the structural deprivation of the rights to an adequate standard of living, safe housing, and a healthy environment for affected populations. While the economic benefits of land exploitation are concentrated among corporations and the state through fiscal revenues, the ecological and social burdens—such as flash floods, damage to settlements, and the loss of livelihoods, are borne by communities who have no control over land-use decision-making.